The Mexican Exception - Williams, G. author. aut Link
VII, 219 p.
Keywords: This book examines the question of democracy in post-revolutionary Mexican society. Each chapter recuperates an event or particular historical sequence that sheds light on the relation between culture and sovereign exceptionality. Each moment or sequence stages a relation to language. In these speech scenes there is a disagreement between social actors (for example, disputes between peasants and intellectuals over words such as democracy, equality, freedom, proletariat, worker, revolution etc.). Democracy in this book is not just a type of Constitution or a form of society that politics affirms on a daily basis. It is the assumption and installation of egalitarian language. Democracy is therefore the momentary interruption or suspension of the police order.